Borderlands : comparing border security in North America and Europe - Brunet-Jailly, Emmanuel, 1961- (Governance series., 2007)
Border security has been high on public-policy agendas in Europe and North America since the September 11, 2001 attacks on the World Trade Centre in New York City and on the headquarters of the American military in Washington DC. Governments are now confronted with managing secure borders, a policy objective that in this era of increased free trade and globalization must compete with intense cross-border flows of people and goods. Border-security policies must enable security personnel to identify, or filter out, dangerous individuals and substances from among the millions of travelers and ton.